Operant conditioning of GSR amplitude under feedback and non-feedback situations - Reyes, Renato B. ([Metro Manila] Psychological Association of the Philippines, 1971)
An experiment was conducted to test two hypotheses: (1) that operant conditioning of GSR would be successful and comparable under both feedback and nonfeedback conditions, feedback being defined as giving the subject an indication of his GSR activity; and (2) that conditioning would be greater under a condition wherein positive reinforcement was clearly appetitive rather than under conditions where positive reinforcement was not clearly appetitive. The appetitive reinforce used was money. A 2 x 2 factorial design used four groups (A, B,C, and D) of 21 Ss each to make a total of 84 Ss. The results of the experiment indicated that feedback may not be a critical factor in operant conditioning of GSR; however, it is pointed out that this finding does not form conclusive proof that the feedback hypothesis does not hold since it is difficult to generalize the results of any single experiment to apply to the whole class of autonomic behaviors.
Includes bibliographical references.
Keywords: Automatic control; Dissertations, Academic -- Philippines; Psychology Philippines -- Periodicals